An Efficient Functionalization Method for the Multiwalled Carbon Nanotubes and Their Applications in PMMA Bone Cement - Yongzhi Xu (Sensors & Transducers, 2013)
In this work, an efficient procedure for the functionalization of multiwalled carbon nanotube (MWCNTs) based on nitric acid oxidation was presented. The morphologies of MWCNTs oxidized under various conditions were characterized by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The FTIR provided clear evidence for the presence of carboxylic groups (–COOH) attached to the surface of MWCNTs resulting from the acid treatment. The unfunctionalised MWCNTs(p-MWCNTs) and carboxy1 functionalized MWCNTs (f-MWCNTs) were successfully applied into the Polymethyl methacrylate (PMMA) bone cement. The resultant mechanical experiment indicated that the f-MWCNTs were a promising additive to improve the compressive strength and bend strength of the PMMA bone cement. The morphology and degree of dispersion of the MWCNTs in the PMMA matrix at different scales were analyzed by SEM. Improvements in mechanical properties were attributed to the MWCNTs arresting or retarding crack propagation through the cement by providing a bridging effect into the crack, normal to the direction of crack growth.